Revealing Students’ Barriers and Strategies during Performing Presentation: Evidences from the Field - Karin, Vanesa; Yulistiyanti, Yulistiyanti; Abrori, Rafila Kasamira Dewi (Dinamika Bahasa dan Budaya, 2025)
This research investigates students' experiences during presentations, focusing on the challenges they face and the strategies they employ to overcome them. The study aims to provide deeper insights into the barriers students encounter when presenting, as well as the strategies they use to address these challenges effectively. The research uses a qualitative approach, with data collected from six students in the English department at a university in Central Java through online interviews. The results of the study reveal that the participants face several barriers, such as the fear of judgment, physical symptoms of anxiety, uncertainty about the topic, and difficulties in creating effective and interactive presentation media. To overcome these obstacles, the participants use various strategies, including thorough preparation (such as creating PowerPoint slides), practicing their presentations, and seeking feedback from peers or instructors. Other strategies involve using self-affirmation, incorporating humor or jokes to engage the audience, and snapping fingers to help refocus and break awkward moments. These findings highlight the importance of preparation and coping mechanisms to manage anxiety and ensure effective communication during presentations.